Fracture Resistance of Endodontically Treated Premolars Reconstructed by Traditional Casting and CAD-CAM Milling Post and Cores - Davood Nodehi; Azizollah Moraditalab; Shahrzad Shafiee; Salehe Sekandari; Farzaneh Ahrari (Hindawi Limited, 2022)
Purpose. Restoration of endodontically treated premolars has always been considered as a challenging procedure. This study compared the fracture strength and mode of failure of root canal treated premolars reconstructed with various post and core systems. Materials and Methods. Twenty healthy extracted premolars were selected and underwent root canal treatment and then randomly assigned into 4 groups (n = 5). The teeth in group 1 restored with amalgam, whereas others reconstructed with post and cores made by cobalt-chromium (Co-Cr) casting (group 2), nonprecious gold (NPG) casting (group 3), or computer-aided design (CAD) and computer-aided manufacturing (CAM) milling (group 4). The force at fracture was measured in a universal testing machine, and the failure mode was recorded as repairable or nonrepairable. Results. ANOVA revealed a significant difference in fracture resistance between groups (P=0.001). The control group displayed significantly lower strength than that of the CAD-CAM or CO-Cr groups (P<0.05). The CAD-CAM posts were also more resistant to fracture than the NPG group (P<0.05). The frequencies of repairable fracture in the control, Co-Cr, NPG, and CAD-CAM groups were 40%, 20%, 20%, and 60%, respectively. The chi-square test revealed no significant difference in the distribution of failure modes between groups (P=0.415). Conclusion. The teeth reconstructed with post and cores were more resistant to fracture than those restored with amalgam alone. CAD-CAM milling could be considered as the best system for reconstruction of endodontically treated teeth, as it provided the highest fracture strength with less risk of nonrepairable tooth fracture.